Exploring the role of loneliness, depression, and ideal self-image congruence on online game addiction: psychological ownership as mediating variable - Sutat Manalom Sadewa; Chairy Chairy (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Online gaming has become a popular form of electronic entertainment for people around the world. However, the growing reputation of online gambling can lead to addiction in certain situations. This is a topic that has received a lot of attention. The purpose of this research is to bring the meaning of psychological ownership as a joint mediator of loneliness, depression, and psychological ownership closer to video game addiction (OGA). Using the partial least squares structural equation modeling technique, we tested the survey model for 154 valid responses from a Google Forms survey. Searches show that depression and ideal self-image are undoubtedly related to the psychological responsibility of online game addiction. The curvilinear relationship between psychological ownership and OGA means that higher psychological ownership is associated with better OGA. This study provides practical advice and solutions to address the OGA's growing concern. In the first place, their environment must encourage them to participate in external activities consisting of sports tournaments and offline cosplay video games to help them overcome loneliness and take ideal images, not 2d, families should know that OGA exists in their homes. OGA could be the way they deal with depression. In addition, this is the first study to investigate the horrifying aspects of a gambling organization that lends out spiritual property to keep players hooked on the game.